EFFECTIVENESS OF THE SCOUT PROGRAM IN INCREASING STUDENT INDEPENDENCE AT SMP NEGERI 18 BANDA ACEH - zir, Mun; irwandi, irwandi; Hariansyah, Septi (Universitas Syiah Kuala, 2024)
This research aims to evaluate the effectiveness of the Scout program in increasing student independence at SMP Negeri 18 Banda Aceh. The research method used is descriptive research with a qualitative approach. Data was collected through observation, interviews and analysis of documents related to the Scout program and student independence. The research results show that the Scout program is effective in increasing student independence through developing social skills, leadership and practical knowledge. Students who are active in Scouting activities have a higher level of independence in overcoming challenges, working in teams, and taking initiative. The importance of the Scout program in the school curriculum is to strengthen students' character learning and independence.Keywords: Effectiveness, Scouts, Independence.